Population structure of the Higaunon tribe of Rogongon, Iligan City - Demayo, Cesar G.; Quijoy, D'Vincet; Torres, Mark Anthony J. (2003)
This study was conducted to learn the population structure of the indigenous peoples of Rogongon, Iligan City, the Higaunons. The group consisted of true-blooded Higaunons and those who are the children of a Higaunon - Christian/ Muslim marriage, the Kulibugans. Survey of nine Mendelian genetic traits, demographic factors, diseases prevalence, and family planning practices of the women were conducted. Results revealed homozygous recessive genotypes are prevalent in the populations of both pure Higaunons and the Kulibugans based on nine traits. Genetic disorders and susceptibility to diseases like tuberculosis and high infant mortality were also observed in the tribe and pedigree analysis indicates genetic control of the disorders and predisposition of the individuals to the disease. The women were also observed to have large numbers of children and it is feared that the frequency of the disorders will increase based on the high reproductive potential of the women.
Keywords: Higaunon people; Higaunon--Indigenous peoples